2015
DOI: 10.1038/srep18212
|View full text |Cite
|
Sign up to set email alerts
|

Degassing during quiescence as a trigger of magma ascent and volcanic eruptions

Abstract: Understanding the mechanisms that control the start-up of volcanic unrest is crucial to improve the forecasting of eruptions at active volcanoes. Among the most active volcanoes in the world are the so-called persistently degassing ones (e.g., Etna, Italy; Merapi, Indonesia), which emit massive amounts of gas during quiescence (several kilotonnes per day) and erupt every few months or years. The hyperactivity of these volcanoes results from frequent pressurizations of the shallow magma plumbing system, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
(46 reference statements)
1
52
0
Order By: Relevance
“…Degassing causes notable depressurization and increase in viscosity of the silicic magma in the chamber (Girona et al 2014(Girona et al , 2015. This process decreases the dynamic of the dacitic magma chamber, acting as a density filter.…”
Section: Eruption Scenarios and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Degassing causes notable depressurization and increase in viscosity of the silicic magma in the chamber (Girona et al 2014(Girona et al , 2015. This process decreases the dynamic of the dacitic magma chamber, acting as a density filter.…”
Section: Eruption Scenarios and Mechanismsmentioning
confidence: 99%
“…In cases where there is no evidence for pre-eruptive degassing, explosive-effusive transition can be also controlled by injection and admixing of recharge magma into the shallow silicic magmatic system (Ruprecht and Bachmann 2010). Recently, it has also been suggested that persistent passive degassing itself could foster magma replenishment and even trigger new eruptions (Girona et al 2014(Girona et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we will explore how the two-way coupling of the hydrothermal magmatic system affects the eruption dynamics and the thermohydromechanical response of the crust. We note that some recent studies (Girona et al, 2014(Girona et al, , 2015 have shown, using primarily mechanical models, that passive degassing has an essential effect on the pressure buildup of magmatic reservoirs in the context of open-vent conduit systems. Our study extends this analysis to more a general magmatic architecture and also incorporates a more comprehensive thermomechanical model for the temporal evolution of melt, especially the release of magmatic volatiles as the magma crystallizes or ascends to shallower depths.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 83%
“…Finally, from a magma reservoir perspective, previous studies have shown that magmatic volatiles play a vital role in modulating the temporal evolution of magma and the buildup of overpressure required for eruption (Degruyter & Huber, 2014;Karlstrom & Richards, 2011). However, few studies have incorporated a direct coupling of magmatic and hydrothermal systems, modulated by the magmatic volatiles (Black & Manga, 2017;Girona et al, 2015;Iguchi et al, 2002;Simakin & Botcharnikov, 2001). The loss of volatiles will significantly affect the fluid pressure within the volcanic system, leading to depressurization of the magma reservoir over time as well as affecting the stress state of the background crust.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
See 1 more Smart Citation